Pembelajaran Keterampilan Berbicara Dengan Metode Field Trip Pada Peserta Didik Kelas IX SMP Samarinda - Sri Mulyo; Mohammad Ilyas; Ahmad Ridhani (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2019)
The learning method, especially in speaking skill learning, is less varied, consequently the learning process tends to be unable to explore the student’s competence in speaking. Therefore, the researcher sees the need to develop FT-V learning method. The objective of this study is to develop FT-V learning method for the ninth graders in Madina integrated Islamic junior high school Samarinda. This study uses Research & Development (R&D) method by using development proposed by Brog and Gall which includes 10 develipments steps. The data sources in this study are nine grade students in Madina integrated Islamic junior high school Samarinda. Data collection is done by means of sequencing, tests, observations, interviews, and documentation. The development of this learning method was declared very feasible by both validators, namely expert validator of learning method and Practitioners. Based on the results of the field tests, FT-V method was also considered to be able to increase the value of student learning outcomes through a field test process. The observation results of student’s learning activities by observer I and II stated very well.